2019
DOI: 10.1101/801084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demographic performance of European tree species at their hot and cold climatic edges

Abstract: 21Species range limits are thought to result from a decline in demographic performance because 22 of unsuitable climate at the edges. However, recent studies reporting contradictory patterns in 23 tree species demographic performance at their edges cast doubt on our ability to predict climate 24 change impacts on species ranges. Here we parameterised integral projection models with climate 25 and competition effects for 27 tree species using forest inventory data from over 90,000 plots across 26 1 Europe. Then… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Widely available data on forest growth and mortality have allowed a good understanding of how tree growth and survival respond to climate fluctuations (Berdanier & Clark, 2016; Brienen et al, 2020; Manzanedo et al, 2020; McMahon et al, 2010; Young et al, 2017). By contrast, an understanding of climate change impacts on fecundity is less developed, as seed production is not directly observed for most species and habitats, and data accumulate slowly and with substantial investment (Clark et al, 2021; Kunstler et al, 2021). Thus, realistic estimates of tree fecundity and population growth rate are basically absent from most vegetation models (Kunstler et al, 2021; McDowell et al, 2020; Vacchiano et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Widely available data on forest growth and mortality have allowed a good understanding of how tree growth and survival respond to climate fluctuations (Berdanier & Clark, 2016; Brienen et al, 2020; Manzanedo et al, 2020; McMahon et al, 2010; Young et al, 2017). By contrast, an understanding of climate change impacts on fecundity is less developed, as seed production is not directly observed for most species and habitats, and data accumulate slowly and with substantial investment (Clark et al, 2021; Kunstler et al, 2021). Thus, realistic estimates of tree fecundity and population growth rate are basically absent from most vegetation models (Kunstler et al, 2021; McDowell et al, 2020; Vacchiano et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, while the lower elevation species F. sylvatica and A. alba might ultimately be the stronger competitors, according to the simulations they are very slow to invade established stands of higher elevation species (mostly P. abies ). Therefore, the abiotic and demographic processes responsible for the limitations at the leading and the trailing edge of a species distribution likely differ considerably leading to complex interactions among species (Kunstler et al 2019; Shi et al., 2020). At higher elevations, environmental harshness can repeatedly reduce growth of ‘non‐treeline’ species such as F. sylvatica (synthesized by Packham, Thomas, Atkinson, & Degen, 2012), which reduces their competitiveness (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, competition might have an important role at the northern border of certain species through its influence on demography. The effects of competition at range edges have recently been investigated for European trees, with a different outcome: competition was a strong determinant of vital rates, but its effect was not stronger at the edge than at the centre of the distribution (Kunstler et al., 2020). Despite this response, the authors also found a weak support for declining performance at the range edge (the abundant‐centre hypothesis).…”
Section: Discussionmentioning
confidence: 99%
“…One way to acknowledge our incomplete understanding or the high degree of variability in demography is to use stochasticity in modelling processes, at the cost of losing the analytical population growth rate. Integral projection models (IPMs) are stage‐ or size‐structured models, like ours, and are promising tools to model forest dynamics (Kunstler et al., 2020; Merow et al., 2014; Vindenes et al., 2012). IPMs can integrate stochasticity into demography, which is a major feature, because chance plays a significant role in lifetime reproductive success variance and, by extension, in the variance of R0 (Snyder & Ellner, 2016, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation